Assessing liquidity to improve bank’s profitability : An applied research - in a number of – Iraqi private banks - HELU, Sana Hassan (Journal of Economics and Administrative Sciences, 2020)
The current research aims to evaluate liquidity (as an independent variable) to improve the bank’s profitability (as a dependent variable ), by the bank’s ability to maximize its profits from its business results without excessive bank’s  liquidity, so that may affect negatively affects the bank’s reputation and it’s dealers confidence in facing their financial obligations. and this may lead trying to come out among other recommendations including contributing to obtain, the bank’s ability to achieve liquidity balance to maximize its profits. This research has been applied to the sample induced intentionally by choosing three Iraqi private banks. The researcher used financial indicators to assess the bank’s liquidity and profitability as the main tool to measure the level of research variables and correlation relationships and influence among them, in order to processing data and information was used statistical analysis program(SPSS) to reach a number of results including the increase in cash compared to deposits which constituted a large percentage. In addition, there is a weak moral correlation. The researcher has between liquidity and profitability, arrived several conclusions strengthen the bank’s performance.